Local arginase inhibition does not modulate cutaneous vasodilation or sweating in young and older men during exercise - Meade, Robert D. (J Appl Physiol (1985), 2019)
Age-related impairments in cutaneous vascular conductance (CVC) and sweat rate (SR) during exercise may result from increased arginase activity, which can attenuate endogenous nitric oxide (NO) production. We therefore evaluated whether arginase inhibition modulates these heat-loss responses in young (n = 9, 23 ± 3 yr) and older (n = 9, 66 ± 6 yr) men during two 30-min bouts of moderate-intensity cycling (Ex1 and Ex2) in the heat (35°C). CVC and SR were measured at forearm skin sites perfused with 1) lactated Ringer’s (control), 2) N(G)-nitro-(L)-arginine methyl ester (L-NAME; NO synthase-inhibited), or 3) N(ω)-hydroxy-nor-arginine and S-(2-boronoethyl)-l-cysteine (Nor-NOHA + BEC; arginase-inhibited). In both groups, CVC was reduced at L-NAME relative to control and Nor-NOHA + BEC (both P < 0.01). Likewise, SR was attenuated with L-NAME compared with control and Nor-NOHA + BEC during each exercise bout in the young men (all P ≤ 0.05); however, no influence of treatment on SR in the older men was observed (P = 0.14). Based on these findings, we then evaluated responses in 7 older men (64 ± 7 yr) during passively induced elevations in esophageal temperature (∆T(es)) equal to those in Ex1 (0.6°C) and Ex2 (0.8°C). L-NAME reduced CVC by 18 ± 20% CVC(max) at a ∆T(es) of 0.8°C (P = 0.03) compared with control, whereas Nor-NOHA + BEC augmented CVC by 20 ± 18% CVC(max), on average, throughout heating (both P ≤ 0.03). SR was not influenced by either treatment (P = 0.80) Thus, arginase inhibition does not modulate CVC or SR during exercise in the heat but, consistent with previous findings, does augment CVC in older men during passive heating. NEW & NOTEWORTHY In the current study, we demonstrate that local arginase inhibition does not influence forearm cutaneous vasodilatory and sweating responses in young or older men during exercise-heat stress. Consistent with previous findings, however, we observed augmented cutaneous blood flow with arginase inhibition during whole-body passive heat stress. Thus, arginase differentially affects cutaneous vasodilation depending on the mode of heat stress but does not influence sweating during exercise or passive heating.